As origens da filosofia crítica: um estudo sobre o tema do espaço nos anos 1768 e 1769 e de sua importância para Kant - Amaral, Lucas Alessandro Duarte (2013)
The present work aims to investigate the space theme in two years of Kant s thought, namely, 1768 and 1769. Undoubtedly, this brief period collaborated decisively to the mature doctrine of the philosopher concerning the subject, as we intend to show in this dissertation. Thus, in order to fulfil such task, it was made a division in three stages. In a first moment, it will be exposed the context in which this theme is inserted, which aims to address some of the aspects of Leibniz s and Newton s positions around the theme, as well the influence of both in a few earliest writings of the philosopher of Königsberg. Then, in the chapter 2, it will be exposed the opuscule of 1768, a famous writing in which Kant breaks definitively with a notion that was defended by himself in his youth: the notion of relative space, passing to accept the Newtonian thesis of absolute space. Finally, in the chapter 3, from a brief but well known Reflection of the philosopher, it will be exposed a new and determinant theory concerning the space. This one, different from that first (i.e., of the young Kant), as well from that other one founded in the opuscule of 1768, therefore, showing this time a doctrine bit more close of what Kant asserts about the space, for instance, in the Transcendental Aesthetics of the Critique of Pure Reason